User Satisfaction Evaluation of Meta AI Integration in WhatsApp: A Quantitative EUCS Approach - Buana, Pratama Angga; Prasetyo, Yekti Adi; Muhsinin, Muhammad; Riza, Muhammad Said; Arif, Ahmad Maulana; Prakoso, Andika Timur (Redtech Putra Benua, 2024)
This study aims to evaluate user satisfaction with the integration of Meta AI technology in the WhatsApp application using the End User Computing Satisfaction (EUCS) model. The model encompasses five key dimensions: Content, Accuracy, Format, Ease of Use, and Timeliness. Data was collected through questionnaires distributed to 44 respondents consisting of students, with the sample determined using the Slovin formula. The analysis revealed that overall user satisfaction falls into the